2023
DOI: 10.3389/fphys.2022.992655
|View full text |Cite
|
Sign up to set email alerts
|

The effects of velocity-based versus percentage-based resistance training on athletic performances in sport-collegiate female basketball players

Abstract: Introduction: The study compared the effects of 6-week (2 sessions/week) velocity-based resistance training (VBRT) and percentage-based resistance training (PBRT) on athletic performance in Sport-College female basketball players.Methods: Fifteen participants were assigned to the VBRT (n = 8) or PBRT (n = 7) groups. The load in VBRT group were determined through the sessional target velocity and velocity loss monitoring, whereas PBRT group used a fixed-load based on percentage of 1-repetition maximum (1RM). Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
0
9
0
5
Order By: Relevance
“…On the other hand, contrary to the second hypothesis, the implemented exercise interventions induced similar muscle damage at each analyzed phase. Indeed, numerous studies compared the efficiency of VBT and PBT programs concerning various neuromuscular performances [ [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. More precisely, available scientific evidence is partially consistent with the findings of the presented study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, contrary to the second hypothesis, the implemented exercise interventions induced similar muscle damage at each analyzed phase. Indeed, numerous studies compared the efficiency of VBT and PBT programs concerning various neuromuscular performances [ [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. More precisely, available scientific evidence is partially consistent with the findings of the presented study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a meta-analysis conducted by Liao et al [ 23 ] did not reveal statistically significant differences between VBT and PBT regarding effects on absolute strength, explosive strength, and speed. Moreover, no statistically significant differences in 1RM squat were observed between VBT and traditional strength training modality in the sport-collegiate female basketball players [ 25 ]. In addition, in line with the results obtained in this investigation, speed-based strength training elicited greater improvements in jump performances of female athletes, including CMJ and SJ tests relative to the PBT program.…”
Section: Discussionmentioning
confidence: 99%
“…During the intervention, players were verbally instructed to perform each repetition at their maximum velocity for strength exercises (Weakley et al, 2020). In this way, both the intensity and the intra‐sets volume were monitored with a linear velocity transducer (Vitruve™, Madrid, Spain) (Pérez‐Castilla et al, 2019), since it has shown to be the most effective control method (Benavides‐Ubric et al, 2020; Dorrell et al, 2020; Sánchez‐Medina et al, 2017; Zhang et al, 2022). Regarding the intra‐set volume of the plyometric exercises, a low volume was sought (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The DJ was performed from a 40 cm wooden box, as recommended by previous study [24]. The DJ protocol began with the athlete standing on the box with hands fixed on the hips for the entire protocol to eliminate the arm swing influence.…”
Section: Lower-body Powermentioning
confidence: 99%